Diabetic Remission in a Mixed Breed Feline – Report of Case (Global Journal of Medical Research, 2023)
Diabetes Mellitus DM is a syndrome characterized by persistent hyperglycemia due to the lack of insulin or the incapacity of exerting its metabolic effects Along with hyperthyroidism it is one of the most common endocrine diseases in felines with obese cats having 3 9 x more chance of developing DM comparing to a cat in an ideal body condition score This report describes the case of a feline female 5- year-old spayed mixed breed with a history of obesity prior body condition score 8 9 presenting weight loss and polyphagy The history of previous obesity associated with the clinical manifestations suggested the possibility of DM which was confirmed due to hyperglycemia glycosuria and the increase of fructosamine values It was instituted therapy using insulin Glargine supporting diet for obesity and environmental enrichment with remission of DM
Keywords: diabetes mellitus; felines; obesity; insulin resistance